2002
DOI: 10.1007/s00442-002-0933-5
|View full text |Cite
|
Sign up to set email alerts
|

An experimental examination of colonization as a generator of biotic nestedness

Abstract: Species assemblages of systems of islands and other fragmented habitats frequently show a "nested-subset" structure in which the biotas of sites with low species richness are non-random subsets of the biotas of richer sites. Much literature suggests that extinction is more likely to produce strongly nested patterns than colonization, although very few experiments have been conducted on the generation of nested-subset patterns. Here, we describe an experiment on nestedness of benthic invertebrates occupying roc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 36 publications
2
40
0
1
Order By: Relevance
“…Similarly, Tscharntke and Kruess (1999) found that SA curves for parasitoid species were steeper than for herbivores, although Steffan-Dewenter (2003) failed to find any difference between bees, wasps and their natural predators and parasitoids. Interestingly, recent analyses of nested communities, in which the composition of speciespoor communities are hierarchically arranged, non-random subsets of species-rich communities (Patterson, 1987) show that species extinction occurs in a consistent, sequential pattern as fragment area decreases (Wright et al, 1998;Lövei & Cartellieri, 2000 ;Loo, Mac Nally & Quinn, 2002), indicating a gradient in extinction vulnerability among species. To date, attempts to integrate the study of nested communities with theoretical predictions of extinction susceptibility for species with particular trait complexes have been largely ad hoc, although this emerging field of research promises to shed further light on area-related extinction patterns.…”
Section: Confounding Factors In the Detection Of Fragmentation Imentioning
confidence: 99%
“…Similarly, Tscharntke and Kruess (1999) found that SA curves for parasitoid species were steeper than for herbivores, although Steffan-Dewenter (2003) failed to find any difference between bees, wasps and their natural predators and parasitoids. Interestingly, recent analyses of nested communities, in which the composition of speciespoor communities are hierarchically arranged, non-random subsets of species-rich communities (Patterson, 1987) show that species extinction occurs in a consistent, sequential pattern as fragment area decreases (Wright et al, 1998;Lövei & Cartellieri, 2000 ;Loo, Mac Nally & Quinn, 2002), indicating a gradient in extinction vulnerability among species. To date, attempts to integrate the study of nested communities with theoretical predictions of extinction susceptibility for species with particular trait complexes have been largely ad hoc, although this emerging field of research promises to shed further light on area-related extinction patterns.…”
Section: Confounding Factors In the Detection Of Fragmentation Imentioning
confidence: 99%
“…As nestedness can be related to assemblage stability (Atmar and Patterson 1993), this could be expected to increase with hydroperiod length due to the presence of species which require more time to complete their life cycles which are not able to survive even occasional dry phases. The temporal variability of nested patterns in biological communities can shed light on the role of colonization and extinction in generating nestedness (Patterson 1990;Loo et al 2002;Bloch et al 2007), and the temporal cycle of wetting and drying in ephemeral waters makes them an ideal system in which to explore such processes. Despite this, no studies to date have explored temporal variation in nestedness in these systems over their wetting/drying cycles.…”
Section: Introductionmentioning
confidence: 99%
“…全貌 (Wright et al, 1998)。因此, 对于不同栖息地类 型中不同类群的嵌套格局还需要进一步的分析和 研究。 目前已有很多机制用来解释嵌套格局的形成 原 因 (Schoener & Schoener, 1983;Blake, 1991;Baber et al, 2004;Higgins et al, 2006), 主要有 4 种假 说在当前占主导地位 (Wright et al, 1998;Chen & Wang, 2004) : (1) 选择性迁移假说(the selective colonization hypothesis):由于物种扩散能力的差异, 扩散能力强或弱的多数物种都可占领大岛屿; 而扩 散能力强的少数物种占领小岛屿,从而形成嵌套格 局 (Bird & Boecklen, 1998;Cook & Quinn, 1995;Conroy et al, 1999;Loo et al, 2002;Mac Nally et al, 2002)。(2) 选择性灭绝假说(the selective extinction hypothesis): 岛屿面积大小制约物种分布, 要求较大 的最小面积的物种,或具有较小种群的物种, 可能 会从不同面积的岛屿生境中首先灭绝, 从而形成嵌 套格局 (Patterson & Atmar, 1986;Bolger et al, 1991;Cutler, 1991;Lomolino, 1996)。 (3) 生境嵌套假说 ( the habitat nestedneass hypothesis):物种分布与生 境密切相关,即嵌套格局是岛屿生境结构呈现嵌套 格局的结果 (Blake, 1991;Calmé & Desrochers, 1999;Honnay et al, 1999;Ficetola & Bernardi, 2004)。 (4) 被动抽样假说(the passive sampling hypothesis):不 同生境中, 物种多度存在较大差异,因此在抽取样 本时,多度高的物种被抽中的概率大; 在不同取样 面积下, 数量丰富的物种在小面积中出现的概率和 在大面积的抽样中出现的概率都大,反之亦然。 因此, 不同取样面积的一系列物种组合自然就形成了嵌 套结构 (Cutler, 1994;Lomolino, 1996;Andrén, 1994;Nielsen & Bascompte, 2007)。4 种假说中, 除"被动 抽样"与物种间多度差异和抽样强度有关 (Schouten et al, 2007) Wright et al, 1998;Fleishman et al, 2002;Schouten et al, 2007)。 在自然生态系统中, 两栖爬行类占有重要地 位。研究表明, 全球两栖爬行类正以超过自然灭绝 的高速率灭绝 (Stuart et al, 2004;Whitfield et al, 2007), 这与生境丧失和片段化有直接关系 (Chen & Li, 1990;Pan et al, 2002 …”
unclassified